Somatopedické simulační techniky a intervence Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Opatřilová, Dagmar (Masaryk University Press, 2018)
Title in English: Stimulation techniques and intervention in education of individuals with physical impairment Limited and disordered movement or ability to move has an impact on the educational process and vocational training of the people with physical disability. Together with the inclusive trends in the society it is necessary to create resources which enable to teachers, assistants and leisure time teachers to work with people with physical disability. The base of presented e-book is aimed on the support including the educational process and the aim is to summarise and present possible intervention and compensation. The studying text should make the orientation in the presented field easier and provide support to students and special needs teachers and to other specialists to solve the problems in the sphere of support of people with physical disability.